Use of Extracellular Monomeric Ubiquitin as a Therapeutic Option for Major Depressive Disorder - José Luis Maldonado-García; Lissette Haydee García-Mena; Danelia Mendieta-Cabrera; Gilberto Pérez-Sánchez; Enrique Becerril-Villanueva; Samantha Alvarez-Herrera; Toni Homberg; Luis Vallejo-Castillo; Sonia Mayra Pérez-Tapia; Martha C. Moreno-Lafont; Daniel Ortuño-Sahagún; Lenin Pavón (MDPI AG, 2024)
Major depressive disorder (MDD) is a mood disorder that has become a global health emergency according to the World Health Organization (WHO). It affects 280 million people worldwide and is a leading cause of disability and financial loss. Patients with MDD present immunoendocrine alterations like cortisol resistance and inflammation, which are associated with alterations in neurotransmitter metabolism. There are currently numerous therapeutic options for patients with MDD; however, some studies suggest a high rate of therapeutic failure. There are multiple hypotheses explaining the pathophysiological mechanisms of MDD, in which several systems are involved, including the neuroendocrine and immune systems. In recent years, inflammation has become an important target for the development of new therapeutic options. Extracellular monomeric ubiquitin (emUb) is a molecule that has been shown to have immunomodulatory properties through several mechanisms including cholinergic modulation and the generation of regulatory T cells. In this perspective article, we highlight the influence of the inflammatory response in MDD. In addition, we review and discuss the evidence for the use of emUb contained in Transferon as a concomitant treatment with selective serotonin reuptake inhibitors (SSRIs).